2014
DOI: 10.1002/jbm.a.35285
|View full text |Cite
|
Sign up to set email alerts
|

Poly(urethane-dimethylsiloxane) copolymers displaying a range of soft segment contents, noncytotoxic chemistry, and nonadherent properties toward endothelial cells

Abstract: Polyurethane copolymers based on α,ω-dihydroxypropyl poly(dimethylsiloxane) (PDMS) with a range of soft segment contents were prepared by two-stage polymerization, and their microstructures, thermal, thermomechanical, and surface properties, as well as in vitro hemo- and cytocompatibility were evaluated. All utilized characterization methods confirmed the existence of moderately microphase separated structures with the appearance of some microphase mixing between segments as the PDMS (i.e., soft segment) conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 56 publications
0
27
1
Order By: Relevance
“…°C for 24 h. Solvent residue was evaporated by drying to constant mass (conditions were vacuum oven (0.5 mmHg), 60 o C, 24 h) as previously described. 25,35 Finally, films of the polymerized materials, approximately 0.2 mm thick, were recovered from their Teflon molds and saved for analysis.…”
Section: Poly(dimethylsiloxane)-based Tpu Nanocomposite Preparation mentioning
confidence: 99%
See 1 more Smart Citation
“…°C for 24 h. Solvent residue was evaporated by drying to constant mass (conditions were vacuum oven (0.5 mmHg), 60 o C, 24 h) as previously described. 25,35 Finally, films of the polymerized materials, approximately 0.2 mm thick, were recovered from their Teflon molds and saved for analysis.…”
Section: Poly(dimethylsiloxane)-based Tpu Nanocomposite Preparation mentioning
confidence: 99%
“…30 We previously studied the fabrication of PDMS-based TPUs as well as their characterization and biocompatibility assessment, and confirmed that the chemical structure and amounts of the soft PDMS segments have a predominant influence on the surface, thermal, thermomechanical and biocompatible characteristics of PDMS-based TPUs. [32][33][34][35][36] We have found that good hemoand cyto-compatibility is related to higher surface roughness, better microphase separation structure, and higher hydrophilicity of these TPUs.…”
Section: Introductionmentioning
confidence: 97%
“…The synthesis of PU copolymers using siloxane-containing prepolymers with PCL and ethylene oxide terminal units has been described [90][91][92][93][94][95][96][97][98]; these terminal units of siloxane-containing prepolymers were used in order to increase the miscibility of polar and non-polar reactants. Thermoplastic PU elastomers based on PDMS were synthesized by a two-step polyaddition procedure in solution, from MDI, 1,4-BD and α,ω-dihydroxy-PCL-b-PDMS-b-PCL [94].…”
Section: Poly(dimethylsiloxane)-based Biopusmentioning
confidence: 99%
“…Potentially biocompatible thermoplastic PUS and PUUS copolymers based on α,ω-dihydroxypropyl-PDMS with different soft segment content have been prepared and characterized [30,97,99]. In these copolymers, the crystallinity, moduli, hydrophilicity, surface free energy and surface roughness increased with decreasing PDMS content.…”
Section: Poly(dimethylsiloxane)-based Biopusmentioning
confidence: 99%
“…7 Elast-Eon is used as a long-term implantable material for cardiovascular applications such as replacement grafts, components of blood pumps, stent coatings, catheters, and orthopedic implants. 8 However, it is inherently incapable of modulating the interactions of cells, including fibroblasts, and, as a consequence, promotes an elevated in vivo fibrotic response that limits its use in tissue repair. 9 A useful approach to improve the biological interaction of synthetic polymers has been to blend them with natural materials.…”
mentioning
confidence: 99%